Innovation Of Batik Design Method Of Arithmetics Line In The Trade Of Riangle In Improving Batik Sales In Lumajang District - Jesi Irwanto (Jurnal Ilmu Manajemen Advantage, 2017)
This research aims to develop a typical batik design lumajang more varied and interesting for consumers by utilizing arithmetic pattern. This is because the typical batik lumajang has a pattern that is monotonous and has a design that is limited enough to make batik lumajang less able to competence with batik from other regions. One of the motifs that are often used by producion of batik lumajang is banana motif and batik semeru motif. On the other hand batik industry competition is quite tight, hail is evidenced by innovative batik designs are growing rapidly from other regions. This makes indutry batik lumajang less well developed. The application of arithmetic method pattern on batik design is expected to add the basic design of typical batik lumajang. The method of this research is done by 5 stages, namely the determination of the basic frame of batik design, setting the position of the point to the triangle frame, constructing the line segment on the triangle frame, filling the motif of the fraction of the triangle frame, the coloring of the base motif of the triangle field.